INTEGRASI MOBILE LEARNING DAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KOMPETENSI SISWA SEKOLAH MENENGAH KEJURUAN - Sugiyanto, - (2020)
This research is based on the need to improve the quality of learning in improving student's competencies through the development of learning models by utilizing smartphones as learning media. The purpose of this research is to develop an instructional model of integration of mobile learning and project-based learning to improve the competency of Vocational High School students on computer assembly and basic network subject. This research uses the Research and Development method and the experimental method at the stage of realizing the design. The subjects of this study were students majoring in Computer and Network Engineering expertise packages at a public vocational high schools in West Java. The research instrument consisted of a questionnaire to determine the need for model development, a competency test and a questionnaire to determine student responses to the developed model. This model was developed and validated by experts and tested on a limited scale and wide scale. Has successfully developed a learning model of integration of mobile learning and project-based learning with the characteristics of the implementation of project-based learning syntax using mobile learning applications to be accessed online through smartphone devices in learning. The result of the assessment by comparing the competence of learning outcomes with N-gain in the high category, as well as the results of the test of the effect size on the increase competence in the cognitive realm of 77%, 94% psychomotor and 84% more effective compared with the results of limited trials. Significant improvement in psychomotor competence, caused there are the level of active participation of students, the direct participation of students, students who have high curiosity and the achieved progress by learning steps in the phases particular to use mobile media applications (smartphones) as learning resources. Learning uses the integration model of mobile learning and project-based learning shows an increase in student competence caused by effective learning, indicated by positive responses from students.